The spillovers, interactions, and (un)intended consequences of monetary and regulatory policies - Kristin Forbes; Dennis Reinhardt; Tomasz Wieladek (Bank of England, External Monetary Policy Committee Unit, 2016)
Have bank regulatory policies and unconventional monetary policies - and any possible interactions - been a factor behind the recent "deglobalisation" in cross-border bank lending? To test this hypothesis, we use bank-level data from the United Kingdom - a country at the heart of the global financial system. Our results suggest that increases in microprudential capital requirements tend to reduce international bank lending and some forms of unconventional monetary policy can amplify this effect. Specifically, the United Kingdom's Funding for Lending Scheme (FLS) significantly amplified the effects of increased capital requirements on external lending. Quantitative easing may also have had an amplification effect, but these estimates are usually insignificant and smaller in magnitude. We find that this interaction between microprudential regulations and the FLS can explain roughly 30% of the contraction in aggregate UK cross-border bank lending between mid-2012 and end-2013, corresponding to around 10% of the contraction globally. This suggests that unconventional monetary policy designed to support domestic lending can have the unintended consequence of reducing foreign lending.
Keywords: G21; G28; 330; Capital requirements; Funding for Lending Scheme; financial deglobalisation; Bankenregulierung; Quantitative Lockerung; Geldpolitik; Wirkungsanalyse; Internationaler Kredit; Großbritannien; Spillover-Effekt; Internationaler Finanzmarkt; Welt